Determinan Sosial Ekonomi Konsumsi Minuman Berpemanis di Indonesia: Analisis Data Susenas 2017 - Daeli, Widi Astutty Casimira; Nurwahyuni, Atik (UI Scholars Hub, 2019)
Sugar-Sweetened Beverages (SSBs) are added liquids with various of sugar. Consumption of SSBs contributes to Non-Communicable Diseases (NCDs) such as weight gain, increasing the risk of type 2 diabetes mellitus and cardiovascular diseases. NCDs can be prevent ed as early as possible by reducing the consumption of calories in sugar. WHO recommends adults and children to reduce sugar intake to less than 10% of total energy intake and continue to less than 5% of total energy intake. This study aims to determine the socio-eco nomic factors consumption of SSBs. We employed secondary data from the 2017 National Socio-Economic Survey (Susenas) with two-part models (OLS, Probit and Tobit). We found that internet access is consistently associated with lower household expenditure and consumption of SSBs. Therefore, it is necessary to increase the promotion of public health service advertising related to the danger of excessive consumption of SSBs and the inclusion of safe consumption of SSBs on packaging labels.